2019
DOI: 10.14202/vetworld.2019.1116-1120
|View full text |Cite
|
Sign up to set email alerts
|

A diluent containing coconut water, fructose, and chicken egg yolk increases rooster sperm quality at 5°C

Abstract: Aim: The present study was conducted to evaluate the quality of rooster sperm at 5°C after treatment with a diluent containing coconut water, fructose, and chicken egg yolk and stored the semen sample at 5°C. Materials and Methods: Ten semen samples from 10 healthy roosters were subjected to four different treatments. For the treatments, 0.2 ml fresh semen with a sperm concentration of 5.2X109 cell/ml was mixed with T0 (no diluent), T1 (0.34 ml coconut water and 6 μl fructose), T2 (0.274 ml coconut water, 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
3
16
0
1
Order By: Relevance
“…This result was in accordance with that the pH of chicken semen was between 7.2-7.6 (Iswati et al, 2018). Massa motility was obtained 3+ which was indicated that it was in accordance with Rochmi & Sofyan (2019) who stated that the excellent mass motility was 3+ and marked by cloud-like huddling sperm. Individual motility and viability produced were greater at 85% and 94.17 ± 1.47% compared to Sun et al, (2019) at 67.84%, 71.17% and (Shanmugam et al, 2014) at 46.25 %, 93.01 ± 2.39%.…”
Section: Results Of Stroage Of Semen Gallus Domesticussupporting
confidence: 82%
See 2 more Smart Citations
“…This result was in accordance with that the pH of chicken semen was between 7.2-7.6 (Iswati et al, 2018). Massa motility was obtained 3+ which was indicated that it was in accordance with Rochmi & Sofyan (2019) who stated that the excellent mass motility was 3+ and marked by cloud-like huddling sperm. Individual motility and viability produced were greater at 85% and 94.17 ± 1.47% compared to Sun et al, (2019) at 67.84%, 71.17% and (Shanmugam et al, 2014) at 46.25 %, 93.01 ± 2.39%.…”
Section: Results Of Stroage Of Semen Gallus Domesticussupporting
confidence: 82%
“…Gallus domesticus has an economic value due to its distinctive taste of meat and egg. Therefore, Indonesians put so much interest and have high demand towards it (Rochmi & Sofyan, 2019). Some advantages of the Gallus domesticus breeding compared to purebreed chicken are including the fact that it is more resistance to the disease, has high adaptability to the environment, as well as its breeding is relatively easier.…”
Section: Abstract a B S T R A K Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The young coconut water diluent with egg yolk contains a nutritional source for spermatozoa metabolism and isotonic properties to semen. It acts as a buffer, protects spermatozoa in the cooling process, and is not toxic (Rochmi and Sofyan 2019;Puja et al 2018). Furthermore, the optimal ratio of young coconut water and egg yolk is 80:20% (Apriliana et al 2021;Priharyanthi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to Qiu, Li, Xie, Li, Dong, Sun, Gao & Tan (2016), spermatozoa metabolize glucose during long-term liquid storage of semen, and this is important not only in the goat but also in other species. Previous researchers have proven the effectiveness of the combination of extenders with carbohydrates on the quality of poultry spermatozoa, for example, Rochmi & Sofyan (2019) found a diluent containing a mixture of coconut water, egg yolk, and fructose can be added to rooster sperm to increase spermatozoa motility and viability for up to 7 days when the cement samples are stored at 5 ° C.…”
mentioning
confidence: 99%